Pemanfaatan AI untuk Membuat Media Pembelajaran Interaktif yang Menarik Bagi Siswa SD - Ulfah Maulidhya; Khusnul Khotimah; Mustamiroh Mustamiroh; Sotinsia Desi Lastari; Auliya Sofy (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
The integration of Artificial Intelligence (AI) in education provides opportunities for teachers to develop more interactive and innovative digital learning media. However, the results of observations and pre-tests conducted at SD Negeri 021 Sungai Kunjang, Samarinda, indicated that most teachers used AI merely as an information-searching tool and lacked adequate skills to develop AI-assisted learning media. This community service program aimed to enhance teachers’ competencies in utilizing AI as a professional partner for developing interactive digital learning media to strengthen students’ literacy and numeracy skills. The program employed a participatory mentoring approach consisting of needs assessment, training sessions, hands-on practice, discussions, evaluation, and the establishment of a teacher learning community. A total of 22 elementary school teachers participated in the program. The results demonstrated significant improvements in teachers’ understanding and skills in designing effective prompts, selecting appropriate AI platforms, and developing digital learning media using ChatGPT, Canva AI, and Zep Quiz. In addition to producing classroom-ready learning materials, the program increased teachers’ confidence in integrating AI into pedagogical practices in an ethical and responsible manner. Program sustainability was supported through the establishment of a Professional Learning Community to facilitate the sharing of best practices and continuous professional development in digital competencies. These findings indicate that practice-based mentoring is an effective strategy for strengthening teachers’ competencies in utilizing AI to foster innovation in elementary school learning.